Spacetime heterogeneity of drought characteristics in Sabah and Sarawak, East Malaysia: implications for developing effective drought monitoring and mitigation strategies - Huang Y.F.; Ng J.L.; Fung K.F.; Weng T.K.; AlDahoul N.; Ahmed A.N.; Sherif M.; Chaplot B.; Chong K.L.; Elshafie A. (Springer Science and Business Media Deutschland GmbH, 2024)
Natural calamities like droughts have harmed not just humanity throughout history but also the economy, food, agricultural production, flora, animal habitat, etc. A drought monitoring system must incorporate a study of the geographical and temporal fluctuation of the drought characteristics to function effectively. This study investigated the spacetime heterogeneity of drought features across Sabah and Sarawak, East Malaysia. The Standardized Precipitation Index (SPIs) at timescales of 1-month, 3-months, and 6-months was selected to determine the spatial distribution of drought characteristics. Rainfall hydrographs for the area for 30years between 1988 and 2017have been used in this study. A total of six five-year sub-periods were studied, with an emphasis on the lowest and highest drought occurrence. The sub-periods were a division of the 30years over an arbitrary continual division for convenience. The results showed that the sub-periods 19931997 and 20082012 had the highest and lowest comparative drought events. The drought conditions were particularly severe in Central and Eastern partsof EastMalaysia, owing to El Nino events and the country's hilly terrain. Understanding how and when drought occurs can aid in establishing and developing drought mitigation strategies for the region. 2023, The Author(s).